ANALISIS TOKOH DAN PENOKOHAN DALAM NOVEL TRAUMA KARYA BOY CANDRA - Margarita Irenius; Martono Martono; Antonius Totok Priyadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstrackThis study aims to describe the analysis of characters and characterizations in the novel Trauma by Boy Candra with a behavioristic psychology which means that changes in behavior as a result of the interaction between stimulus and response. This research uses descriptive method, qualitative research form, and behavioristic psychology approach. The data source in this research is the novel Trauma by Boy Candra. The data in the study are in the form of quotations, words, phrases, and sentences. The data collection technique in this research is a documentary study. Based on the results of data analysis, it can be concluded that. 1) the author describes the main character, namely directly and indirectly. The main characters in the novel Trauma by Boy Candra are Kimara who has a friendly, vindictive, and caring character, 2) the author describes the additional characters in the novel Trauma by Boy Candra, either directly or indirectly. Mother has a caring character, Ardi Sabil has a humble character, Kori Marsandi has a bad- tempered character, Dent Sasindra has a selfish and liar character, Raditio Rahadi has a caring character, Mona has a friendly character, Grandpa has a caring character, and finally the additional character is Putra Marnanda. has a deceitful character. The results of this study can be implemented in learning Indonesian in high school, especially in class XII students in even semesters.Keywords: Behavioristic, Character and Characterization